(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Regular recreational activity has numerous mental, physical, and social health benefits. To examine motivations to engage in recreational activity and perceptions of health by gender and Stage of Change (SOC), an online survey was developed and promoted in the Southeastern region of United States in Spring 2015. Using General Linear Model Analysis of Variance (GLM), motivation to participate in recreational activity and perceptions of health (dependent variables) were examined by the independent variables of gender and SOC (covariate). Participants included 735 adults (58.23% female). Females were more likely than males to use recreational activity “to improve physical health and fitness” (Female: M=1.31, Male: 1.42, p < .05) and “to insure mental health and well-being” (Female: M = 1.42, Male: M = 1.61, p < .001). Females perceived better health than males (Female: M = 2.11, Male: M = 2.20, p <, .05). These same items were also significant by SOC with responses decreasing (more likely to agree) by 15.7% (p< .001), 13.15% (p < .0001) and 26.26% (p < .05) for each unit increase in SOC. Needs assessments conducted in this manner may increase participation by allowing for targeted messages to be created for various population groups.